Pathways of health care for people living with multimorbidity in two Southern African countries - Gift Treighcy Banda-Mtaula; Mtisunge Joshua Gondwe; Nateiya M. Yongolo; Rashida A. Ferrand; Stephen Kasenda; Sara Lowe; Brown David Khongo; Naomi S. Levitt; Beatrice Matanje; Charlotte Taderera; Justin Dixon; Celia L. Gregson; et al. (PLoS ONE, 2026)
Multimorbidity, the presence of multiple chronic conditions in one person, is a growing global health concern. Integration of chronic care services is urgently needed, especially in low-resource settings including in Southern Africa, where care has been fragmented by vertical and siloed disease approaches. Many countries share similar challenges of integration, presenting rich opportunities for shared learning. Yet, rarely are these opportunities capitalised upon, in part because of a lack of systematic knowledge about the similarities and differences in health system contexts, challenges and current progress towards integration. As part of an inter-country collaboration, we sought to answer the questions: What are the common and distinct characteristics of the care pathways for people living with multimorbidity in Malawi and Zimbabwe, and the opportunities and challenges that emerge through such a country-level comparison? We used an iterative, qualitative research design that involved a desk review of relevant indicators, policies and strategies; key informant interviews, collaborative workshops, and the development of case studies of service integration in practice. Thematic analysis and comparison of challenges of integration across different levels of care revealed uneven funding for different diseases, a lack of both ‘vertical’ and ‘horizontal’ integration, frequent stockouts of drugs and diagnostic equipment, especially for noncommunicable diseases (NCDs), and inadequate training and support for clinicians. In both countries, progress towards decentralising and integrating chronic disease care at national level, has occurred through inclusion of specific NCDs into HIV programmes. This is prone to leave out comprehensive chronic care for people that are not living with HIV and reproduces verticalised programming. We suggest that a promising avenue for wider scale-up of decentralised, non-HIV-dependent integrated care lies in the expansion of an Integrated Chronic Care Clinic (IC3) model that provides comprehensive health system integration for all chronic diseases. Further cross-country learning and feasibility assessment is needed to advance this model.